Microclimate without shade and silvopastoral system during summer and winter - doi: 10.4025/actascianimsci.v35i1.15155 (Acta Scientiarum. Animal Sciences, 2012)
This study evaluated the microclimate in a system without shade (WS) and in a silvopastoral system (SP) with eucalyptus during summer and winter, by measuring the air temperature (Ta), black globe temperature (Tg), relative humidity (RH), wind speed (Ws), every 2 hours for 24 hours between rows, shade (SP) and no shade effect (WS). It was employed the randomized blocks design (months), in the plots (systems), subplots (hours) and sub-subplots (seasons). Except for Ta and RH, the Tg (24.73, 26.41ºC), Ws (3.16, 4.57 m s-1), Black globe-humidity index (BGHI) (71.83, 73.84), Thermal load index (TLI) (74.53, 76.11) and Radiant thermal load (RTL) (526.46, 595.80 W m-2), respectively for SP and WS, were higher in WS. Ta, RH and Ws had a quadratic effect of hour. There was an effect of season, respectively in summer and winter, on the Ta (27.55, 14.93°C), RH (72.11, 60.68%), Tg (29.80, 21.33°C), BGHI (80.04, 65.63), TLI (81.64, 69.00) and RTL (575.65, 546.61 W m-2). Tg, RH and RTL showed an interaction of season x hour, and a quadratic effect, and the RTL had an interaction of system x season. The Tg was correlated with BGHI (0.962), TLI (0.956) and RTL (0.809). The silvopastoral system decreased the Tg and Ws, and made the environment more harmonious by decreasing the climatic differences between seasons.